Correlation of Fine Needle Aspiration Cytology and Histopathology Diagnosis in the Evaluation of Breast Lumps - Adnan Khan; Raza Jamali; Muneeb Jan; Maria Tasneem (University Library System, University of Pittsburgh, 2014)
Background: A large number of patients have been suffer from breast cancer worldwide and this trend is increasing. It is difficult to determine whether a lump is benign or malignant from clinical assessment; thus, the need for micropic and tissue analysis arises. Methods: This comparative retrospective cross sectional study was conducted in the Department of Pathology, Rehman Medical Institute, Peshawar, Pakistan from January 2006 to March 2013, to determine the value of fine needle aspiration cytology (FNAC) in the diagnosis of breast lump and to compare the result of FNAC with histological diagnosis to assess its accuracy. Results: Seventy-four cases with breast lumps were presented for FNAC. Of these, 32.4% were reported as a C2 lesion, 4.1% were reported as benign with atypical cells (C3), 8.1% cases were suspicious for malignancy (C4), and 55.4% were positive for malignancy (C5). On histopathology examination, out of 24 cases which were reported as C2 lesions, 95.8% were benign and 4.1% turned out to be invasive ductal carcinoma. Of the cases that presented as C3 lesions, one was diagnosed as benign duct ectasia, one with ductal carcinoma in situ, and one with invasive ductal carcinoma on histopathological examination. The cases that were diagnosed as C4 lesions all turned out to be carcinoma on histopathology. In this study, FNAC and histopathology diagnoses were strongly correlated [r 0.92, p <0.001]. Conclusion: Diagnosis of breast lump based on FNAC should be practiced as there is high correlation with histopathological finding. FNAC should be used as a routine diagnostic procedure due to its cost effectiveness, thus maximizing the availability of effective health care to patients with breast lesions.